Implementation of islamic cultural history learning in motivating student learning activity - Eva Sofwatun Nida; Farhana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The increasing need for more effective and interesting Islamic Cultural History (SKI) learning is the background of this research. This study aims to analyze the implementation and evaluation of SKI learning in motivating student learning activeness at MTs Negeri 5 Cilincing, North Jakarta. Using a qualitative approach, data were collected through interviews, observations, and documentation with two SKI teachers, the principal, and student representatives. The results showed significant differences between 2 approaches, namely the conventional approach (lectures and questions and answers) and the contextual approach with varied methods (discussions, audio-visual media, and field trips). The contextual approach supported by various learning media proved to be more effective in improving students' activeness, motivation and understanding. In addition, a varied and fair teacher evaluation system, along with constructive and personalized feedback, proved more effective in increasing student motivation. To improve the quality of learning, thorough and continuous teacher training, especially in material enrichment and evaluation methods, is essential.